Pharmaceutical Service Standards In Pharmacies In Baubau City - Hasna Rahmawati; Hasty Hamzah; Sitti Alfyanita Ilham (Yayasan Cipta Anak Bangsa (YCAB) Publisher, 2026)
Background: Pharmaceutical services play a critical role in safeguarding public health by ensuring the rational, safe, and effective use of medicines. In Indonesia, the implementation of pharmacy service standards is regulated through the Decree of the Minister of Health of the Republic of Indonesia Number 73 of 2016, which serves as a framework to improve the quality and consistency of pharmaceutical services in community pharmacies. Objectives: This study aimed to assess the extent of compliance with pharmaceutical service standards in community pharmacies in Baubau City. Methods: A descriptive cross-sectional survey with a quantitative approach was conducted in 19 community pharmacies in Baubau City. Data were collected using a structured questionnaire derived from the pharmaceutical service standards stipulated in Minister of Health Decree No. 73/2016. Descriptive statistics were applied to summarize findings in the form of frequencies and percentages across key assessment domains, including human resources, facilities and infrastructure, and service quality. Results: The evaluation indicated that most pharmacies demonstrated adequate implementation of pharmaceutical service standards. Overall, 74% of pharmacies were categorized as “good,” while 26% were classified as “fair/adequate,” based on aggregated performance across the assessed domains. Conclusion: The majority of community pharmacies in Baubau City have implemented pharmaceutical service standards in accordance with Minister of Health Decree No. 73/2016 at a generally good level. However, a proportion of pharmacies still show only adequate compliance, highlighting the need for continuous supervision, capacity building, and quality improvement initiatives to strengthen pharmaceutical service delivery. Keywords: pharmaceutical services; community pharmacy; service standards; cross-sectional survey; Baubau City